Gas leak localization and detection method based on a multi-point ultrasonic sensor array with TDOA algorithm - Tao, Wang; Dongying, Wang; Yu, Pei; Wei, Fan (Measurement science & technology, 2015)
To resolve the measured target position to determine and locate leak problems with current gas leak detection and localization systems based on ultrasonic technology, this paper presents an improved multi-array ultrasonic gas leak TDOA (time difference of arrival) localization and detection method. This method involves arranging ultrasonic transducers at equal intervals in a high-sensitivity detector array, using small differences in ultrasonic sound intensity to determine the scope of the leak and generate a rough localization, and then using an array TDOA localization algorithm to determine the precise leak location. This method is then implemented in an ultrasonic leak detection and localization system. Experimental results showed that the TDOA localization method, using auxiliary sound intensity factors to avoid dependence on a single sound intensity to determine the leak size and location, achieved a localization error of less than 2 mm. The validity and correctness of this approach were thus verified.